Ocular pharmacokinetics of intravitreal conbercept in a rabbit model following retinal scatter laser photocoagulation - Chen, Lanlan; Liu, Hua; Zhang, Qingrong; Huang, Houbin (Frontiers in Pharmacology, 2025)
ObjectiveThe present study aims to evaluate the ocular pharmacokinetics of intravitreal conbercept after retinal scatter laser photocoagulation.MethodsThirty male Chinchilla rabbits (60 eyes) were used in this study. The control and photocoagulated animals received single bilateral intravitreal injections of conbercept, and the ocular tissues were collected and quantified for drug concentration using ELISA. Statistical analysis was then performed to compare the pharmacokinetic parameters between the control and photocoagulated eyes.ResultsThe conbercept concentrations were higher in the control rabbits than the photocoagulated rabbits and reached peak values in all ocular tissues 1 d after intravitreal dosing. The terminal t1/2 values in the vitreous humor (4.36 d), aqueous humor (4.19 d), retina (3.94 d), and choroid-RPE (3.84 d) of the control eyes were longer than those in the photocoagulated eyes (3.82 d, 3.69 d, 3.65 d, and 3.58 d, respectively). Conbercept exposure assessed using AUC0-t was lower in the photocoagulated rabbits than control animals in all four ocular matrices (p < 0.01). The clearance and volume of distribution were greater in the photocoagulated eyes than the control eyes, while the mean residence times were shorter in all four matrices.ConclusionRetinal scatter laser photocoagulation shortly before single intravitreal injection of conbercept enabled higher drug clearance and shorter half-life values, resulting in lower exposure in the ocular tissues compared to non-photocoagulated conditions. The distinct ocular pharmacokinetics of intravitreal conbercept observed in a rabbit model through retinal scatter laser photocoagulation is expected to enlighten further studies on investigating the optimal order of the combination of photocoagulation and anti-VEGF agents.